Effect of age, sex, area and management practices on cattle mortality in Rajshahi division, Bangladesh (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: The aim of the present study was to evaluate the effect of age, sex, location and management on cattle mortality rate in Rajshahi division of Bangladesh. Materials and methods: The study was conducted in 8 districts of Rajshahi division during July 2011 to June 2012. A total of 17,982 cattle heads were investigated based on age, sex, area. Data were collected from the cattle owners using a closed structured questionnaire. Tentative cause of cattle mortality was identified based on clinical signs, laboratory tests, history, ante-mortem and postmortem reports. Management practices of the cattle were also investigated.  Results: Out of 17,982 cattle heads, 549 were found to be dead by various diseases, and an average mortality rate was 3.05%. Age-wise mortality rate of cattle revealed that the maximum mortality rate was found in the age group of